Experimental Study on Steel Slit and Shear Panel for Seismic Resistance. Issue 2 (1st September 2021) - Gashi, Ferit; Bontempi, Franco; Petrini, Francesco
Abstract: This paper summarizes the experimental campaign carried out for the development of new steel energy dissipative devices named Slit Dampers (SDs) designed for earthquake protection of structures. A total of eighty‐two steel shear plates with different openings and thicknesses are tested to investigate their behaviour under cyclic pseudo‐static loading. Eight types of steel shear plates are studied, including the SD with narrow slits that divide the plate into rectangular links, and the butterfly fuse with a diamond‐shaped opening that creates butterfly shape links in the plate. Other varying test parameters are loading rate, material strength, and the number of in‐parallel damper elements. It is expected that the proposed model can be successfully used to predict the behaviour of dampers in real‐world applications.